Effects of an interprofessional communication approach on support needs, quality of life, and mood of patients with advanced lung cancer: a randomized trial - Krug, Katja; Bossert, Jasmin; Deis, Nicole; Krisam, Johannes; Villalobos Bollen, Matthias Americo; Siegle, Anja; Jung, Corinna; Hagelskamp, Laura; Unsöld, Laura; Jünger, Jana; Thomas, Michael; Wensing, Michel (The oncologist, 2021)
To address the support needs of newly diagnosed patients with lung cancer with limited prognosis, the Milestone Communication Approach (MCA) was developed and implemented. The main elements of the MCA are situation-specific conversations along the disease trajectory conducted by an interprofessional tandem of physician and nurse. The aim of the study was to evaluate the effects of MCA on addressing support needs, quality of life, and mood as compared with standard oncological care.A randomized trial was conducted with baseline assessment and follow-up assessments at 3, 6, and 9 months in outpatients with newly diagnosed lung cancer stage IV at a German thoracic oncology hospital. The primary outcome was the Health System and Information Needs subscale of the Short Form Supportive Care Needs Survey (SCNS-SF34-G) at 3-month follow-up. Secondary outcomes included the other subscales of the SCNS-SF34-G, the Schedule for the Evaluation of Individual Quality of Life, the Functional Assessment of Cancer Therapy lung module, the Patient Health Questionnaire for Depression and Anxiety, and the Distress Thermometer.At baseline, 174 patients were randomized, of whom 102 patients (MCA: n = 52; standard care: n = 50) provided data at 3-month follow-up. Patients of the MCA group reported lower information needs at 3-month follow-up (mean ± SD, 33.4 ± 27.5; standard care, 43.1 ± 29.9; p = .033). No effects were found for secondary outcomes.MCA lowered patient-reported information needs but did not have other effects. MCA contributed to tailored communication because an adequate level of information and orientation set the basis for patient-centered care.By addressing relevant issues at predefined times, the Milestone Communication Approach provides individual patient-centered care facilitating the timely integration of palliative care for patients with a limited prognosis. The needs of patients with lung cancer must be assessed and addressed throughout the disease trajectory. Although specific topics may be relevant for all patients, such as information about the disease and associated health care, situations of individual patients and their families must be considered. Additionally, using the short form of the Supportive Care Needs Survey in clinical practice to identify patients’ problems might support individually targeted communication and preference-sensitive care.
Gesehen am 21.08.2023